The right to have a proceeding concluded within a reasonable time obliges the legislator to set a specific time limit for the proceeding - Contreras Campos, Elmer Elías (2023)
This article deals with a subject that in recent years has been part of the discourse of lawyers, judges and even politicians, we refer to the right to be tried within a reasonable time, although we prefer to call it “the right to have a trial concluded within a reasonable time”. But we will not be content with a historical-dogmatic presentation of this right, but will address the problem that we see in the development of trials: without a fixed time limit, the right to have a trial concluded within a reasonable time loses its validity and is sometimes illusory. Therefore, after analyzing the doctrinal proposals, such as the theory of no time limit -which has been adopted by international courts (European Court of Human Rights [ECtHR] and Inter-American Court of Human Rights [IACHR]), as well as the Constitutional Court and the Supreme Court of Peru- and the theory of the fixed time limit, we propose our position, the theory of the fixed time limit set by the legislator, but with the adaptation, on a case by case basis, by the judge. We then move on to the analysis of this right in the civil process, more specifically in the summary proceeding. For this purpose, we developed the scope of the Ninth Plenary Civil Cassation Court, and we call attention to the fact that the supreme judges have not taken into account that the duration of the summary proceeding, in some cases, could be longer than that of an ordinary proceeding, and even adding the duration of the suspended summary proceeding (it was stopped because an aspect of the controversy had to be previously resolved in a knowledge proceeding), which would affect the right to have a proceeding concluded within a reasonable period of time, a situation that has not been noticed by the Supreme Court justices in the aforementioned cassation plenary.